2017
DOI: 10.1016/j.engstruct.2017.05.070
|View full text |Cite
|
Sign up to set email alerts
|

Long-term monitoring of wind field characteristics and dynamic response of a long-span suspension bridge in complex terrain

Abstract: Long-term monitoring data of wind velocities and accelerations on the Hardanger Bridge are used to investigate the relationship between the wind-loading and response processes. The extensive measurement system consisting of 20 accelerometers and 9 anemometers is described as well as the local topography of the site. The wind and response characteristics are presented using scatter plots and wind rose diagrams. The considerable variability observed in the bridge dynamic response is investigated by utilizing res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(35 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…Accelerometer monitoring is an effective means with which to monitor the dynamic characteristics of long-span bridges [1,2]. However, it inevitably causes drift errors as it requires a double integral for acquiring deformation displacement [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Accelerometer monitoring is an effective means with which to monitor the dynamic characteristics of long-span bridges [1,2]. However, it inevitably causes drift errors as it requires a double integral for acquiring deformation displacement [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…This bridge have 20 triaxial accelerometers for measuring the dynamic response, and eight anemometers that measures wind velocities in the main span [28], as shown in Fig. 3.…”
Section: Data From the Hardanger Bridgementioning
confidence: 99%
“…More importantly, their studies can provide references for other long-span bridges in terms of study methods and variations of wind fields at the bridge site. Fenerci et al [17] developed a measurement system consisting of 20 accelerometers and 9 anemometers and used the long-term monitoring data of wind velocities and accelerations on a long-span bridge located in a gorge terrain to investigate the relationship between the wind-loading and responses. Results showed that the wind fields have large variability in the mean wind speed, mean wind direction, turbulence intensities, and length scales in the bridge site.…”
Section: State Of the Artmentioning
confidence: 99%